Clinical and genetic characterisation of infantile liver failure syndrome type 1, due to recessive mutations in LARS. Issue 6 (28th April 2015) - Casey, Jillian P.; Slattery, Suzanne; Cotter, Melanie; Monavari, A. A.; Knerr, Ina; Hughes, Joanne; Treacy, Eileen P.; Devaney, Deirdre; McDermott, Michael; Laffan, Eoghan; Wong, Derek; Lynch, Sally Ann; et al.
Abstract: Background: Recessive LARS mutations were recently reported to cause a novel syndrome, infantile liver failure syndrome type 1 (ILFS1), in six Irish Travellers. We have since identified four additional patients, including one of Ashkenazi origin, representing the largest ILFS1 cohort to date. Our study aims to define the ILFS1 clinical phenotype to help guide diagnosis and patient management. Methods: We clinically evaluated and reviewed the medical records of ten ILFS1 patients. Clinical features, histopathology and natural histories were compared and patient management strategies reviewed. Results: Early failure to thrive, recurrent liver dysfunction, anemia, hypoalbuminemia and seizures were present in all patients. Most patients (90 %) had developmental delay. Encephalopathic episodes triggered by febrile illness have occurred in 80 % and were fatal in two children. Two patients are currently >28 years old and clinically well. Leucine supplementation had no appreciable impact on patient well‐being. However, we suggest that the traditional management of reducing/stopping protein intake in patients with metabolic hepatopathies may not be appropriate for ILFS1. We currently recommend ensuring sufficient natural protein intake when unwell. Conclusions: We report the first non‐Irish ILFS1 patient, suggesting ILFS1 may be more extensive than anticipated. Low birth weight, early failure to thrive, anemia and hypoalbuminemia are amongst the first presenting features, with liver dysfunction before age 1. Episodic hepatic dysfunction is typically triggered by febrile illness, and becomes less severe with increasing age. While difficult to anticipate, two patients are currently >28 years old, suggesting that survival beyond childhood may be associated with a favourable long‐term prognosis.